2021
DOI: 10.1103/physrevapplied.15.064001
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Magnetic Field Amplitude of rf Radiation by the Quasistatic Magnetic Field Effect in Organic Light-Emitting Diodes

Abstract: Electron paramagnetic resonance (EPR) is a versatile tool to probe spin physics in organic semiconductor materials. A common method used to detect the spin-½ paramagnetic resonance in organic light-emitting diodes (OLEDs) is to measure the device resistance under EPR conditions, i.e., to record electrically detected magnetic resonance (EDMR). Here, we present ultralow-frequency EDMR experiments on OLEDs that exhibit a qualitatively new line shape because of a quasistatic magnetic field effect: the modulation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Recently, using magneto‐conductance (MC) as a non‐contact and non‐destructive fingerprint detection tool to visualize ISC and RISC processes and study their physical mechanisms have gained increasing attentions. [ 11–14 ] This is because ISC and RISC processes are highly spin‐dependent and produce fingerprint MC responses which respectively display inverted and upright Lorentzian line‐shapes with several milli‐Tesla around zero magnetic field ( B ) and will be also described in detail in the main text. [ 15–18 ] For example, Chen et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, using magneto‐conductance (MC) as a non‐contact and non‐destructive fingerprint detection tool to visualize ISC and RISC processes and study their physical mechanisms have gained increasing attentions. [ 11–14 ] This is because ISC and RISC processes are highly spin‐dependent and produce fingerprint MC responses which respectively display inverted and upright Lorentzian line‐shapes with several milli‐Tesla around zero magnetic field ( B ) and will be also described in detail in the main text. [ 15–18 ] For example, Chen et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using magneto-conductance (MC) as a non-contact and non-destructive fingerprint detection tool to visualize ISC and RISC processes and study their physical mechanisms have gained increasing attentions. [11][12][13][14] This is because ISC and RISC processes are highly spin-dependent and produce fingerprint MC responses which respectively display inverted and upright Lorentzian line-shapes with several milli-Tesla around zero magnetic field (B) and will be also described in detail in the main text. [15][16][17][18] For example, Chen et al used MC to directly observe the ISC process in EB-OLEDs and found that the ISC process is inversely proportional to the band gap between the highest occupied molecular orbital (HOMO) of the donor and the lowest unoccupied molecular orbital (LUMO) of the acceptor of exciplex states.…”
mentioning
confidence: 99%
“…The difference between the zero-field signal and the Zeeman resonance is supported by an observed RF power dependence; the intensity of the zero-field signal is more sensitive than the Zeeman resonances to the P 50Ω (Figure S3). The zero-field signal can be caused by a quasistatic RF field effect on the dynamics of the e–h pair with a lifetime shorter than the RF period. , In fact, as shown in Figure S4, the photocurrent of the P3HT device decreases upon application of a static magnetic field as large as 0.5 mT in the absence of RF irradiation. In the presence of the weak static magnetic field, the isc among the spin states of the e–h pair (Scheme ) is accelerated, resulting in an increase of the recombination yield (i.e., the so-called low field effect). , …”
Section: Resultsmentioning
confidence: 99%
“…The e–h pair lifetime can be extracted from a spectral simulation based on the e–h pair mechanism, and the e–h pair reaction can be controlled using an optimized RF near zero field . Most recently, the radiowave effect near zero field has been observed in organic light-emitting diodes via electrically detected magnetic resonance (EDMR). The observed radiowave effect on the dark current originates from different actions of the oscillating magnetic field of the radiowave on e–h pairs. The e–h pair with a lifetime shorter than the RF period experiences the oscillating field as a static one.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, while describing MFE response related to the HF interaction mechanism, we term "narrow response" for the response caused by the ultra-lowfield and "wide response" for that caused by the low-field. The ultra-low-field MFE responses as well as the ultralow-frequency EDMR experiments [62,63] have been so far reported in OLED devices; apparently, the reason of this is the long lifetime of the polaron pairs formed out of the electrons and holes injected via the electrodes. This PP long lifetime enables the slow mixing to change the steady state population of the PP S and PP T states.…”
Section: Slow Decay Ratementioning
confidence: 99%